THE EFFECT OF QUIZIZZ-ASSISTED MICROLEARNING METHOD ON STUDENTS’ KNOWLEDGE IN IPAS SUBJECTS AT ELEMENTARY SCHOOL - Wiwik Kristianingsih; Januardi Januardi; Linda Lia (Cerdas Proklamator, 2026)
This study aims to determine the effect of the Quizizz-assisted microlearning method on science learning outcomes of fifth-grade students at SD Negeri 74 Palembang. The research background is the low science learning outcomes due to conventional learning that is less engaging and material presentation that is too lengthy, causing students to become bored quickly. The research method used a Quasi Experimental Design with a Posttest Only Control Group Design. The population was all 53 fifth-grade students in the 2025/2026 academic year with total sampling: class V.D with 25 students as the experimental class and class V.B with 28 students as the control class. The experimental class received Quizizz-assisted microlearning treatment for three meetings on the topic of melting, while the control class used lectures. The instrument was a 20-item multiple-choice test with 15 valid items that were reliable with Cronbach’s Alpha 0.897. Data were analyzed using the Shapiro-Wilk normality test, Levene homogeneity test, and Independent Sample t-test with SPSS 26. The results showed that the experimental class average of 82.396 was significantly higher than the control class of 75.479 with sig. 0.012 < 0.05. It was concluded that there is a significant effect of the Quizizz-assisted microlearning method on science learning outcomes of fifth-grade elementary school students because concise material presentation and interactive evaluation increase student engagement